Pola Makan Sehat Siswa Kelas VII SMP Negeri 34 Medan - Nadra Zelina Putri; Arly Mushlih Hayati Br.Lubis; Syakila Mawaddah Caniago; Zubaidah Lubis; Luqman Hafiz; Khairun Nisa; Mawar Nur Ayu; Siti Nurhalijah; Rehulina Br Sembiring; Adzkia Al Adha Nihayatun Nufus; Lisa Septia Dewi Br. Ginting; Ulian Barus; Dalmi Iskandar Sultani (STIKes Ibnu Sina Ajibarang, 2025)
Nowadays, ready-to-eat food is more popular with teenagers because it is easy and short to serve. Fast food is considered trendy food and is popular among teenagers. Teenagers need to get used to healthy eating patterns to build their bodies. Therefore, research was conducted with the aim of finding out healthy eating patterns for seventh grade students at SMP Negeri 34 Medan. This activity was carried out at SMP Negeri 34 Medan on November 22 2024 in the form of an interview with the theme